Evaluation for Improvement: A Seven Step Empowerment Evaluation Approa ch for Violence Prevention Organizations - Cox, PJ; Keener, D; Woodward, T; Wandersman, A (2009)
This guide, written by Pamela J. Cox, Dana Keener, Tifanee L. Woodard, & Abraham H. Wandersman for the Centers for Disease Control and Preve ntion (CDC) outlines a seven step process for hiring an evaluator to i mplement an empowerment evaluation. The process begins with preparing for the hiring and concludes with an assessment of an evaluation to en sure its sustainability. Excerpt "...concerns and experiences with ind ependent evaluation led to the development of participatory evaluation approaches as a way to promote an organization’s use of evaluation fo r the improvement of its strategies. Although there are many participa tory evaluation approaches, empowerment evaluation places an explicit emphasis on building the evaluation capacity of individuals and organi zations so that evaluation is integrated into the organization’s day-t o-day management processes. Through empowerment evaluation, both indiv idual and organizational evaluation capacity are increased through a “ learn-by-doing” process, whereby organizations and their staff evaluat e their own strategies. Specifically, organizations hire an evaluator to work with them in conducting an evaluation of their strategies. Rat her than evaluating an organization’s strategies and presenting an eva luation “report card,” empowerment evaluators coach individuals and or ganizations through an evaluation of their own strategy(ies) by provid ing them with the knowledge, skills, and resources they need to conduc t just such an evaluation." Contents Empowerment Evaluation: An Overvi ew 11 Principles of Empowerment Evaluation 11 Step 1: Preparing for th e Hiring Process 23 Step 2: Writing a Job Announcement 31 Step 3: Find ing Potential Empowerment Evaluators 39 Step 4: Assessing the Candidat es 45 Step 5: Writing An Evaluation Contract 55 Step 6: Building an Ef fective Relationship With Your Evaluator 61 Step 7: Assessing and Sust aining the Evaluation 65 Appendix A: Resources for General Evaluation and Empowerment Evaluation 73 Appendix B: Worksheets for Hiring an Emp owerment Evaluator 75 Appendix C: Sample Hiring Committee Confidential ity Statement 89 Appendix D: Sample Job 90 Appendix E: Sample Request For Proposals 91 Appendix F: Sample Interview Questions 93 Appendix G: Sample Budget and Narrative for an Evaluation Team 95